2023
DOI: 10.3389/fpls.2023.1196134
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide genotyping data renew knowledge on genetic diversity of a worldwide alfalfa collection and give insights on genetic control of phenology traits

Abstract: China’s and Europe’s dependence on imported protein is a threat to the food self-sufficiency of these regions. It could be solved by growing more legumes, including alfalfa that is the highest protein producer under temperate climate. To create productive and high-value varieties, the use of large genetic diversity combined with genomic evaluation could improve current breeding programs. To study alfalfa diversity, we have used a set of 395 alfalfa accessions (i.e. populations), mainly from Europe, North and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 123 publications
0
4
0
Order By: Relevance
“…Low LD in faba bean was previously reported ( Skovbjerg et al., 2023 ; Zhang et al., 2023 ) when comparing different faba bean diversity panels. Thus, the EUCLEG collection was the one showing lower LD blocks (higher recombination), an expected outcome in outbreeding species with high genetic diversity ( Pégard et al., 2023 ; Skovbjerg et al., 2023 ; Zanotto et al., 2023 ; Zhang et al., 2023 ). The rapid LD decay observed in this study (within roughly 150 kbp) revealed the variation present in a highly allogamous panmictic population and suggested that the MTAs identified (or the closely linked genes on either flanking side of the significant SNPs) were nearly or completely independent from each other and, hence, were sufficient for association mapping in faba bean.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Low LD in faba bean was previously reported ( Skovbjerg et al., 2023 ; Zhang et al., 2023 ) when comparing different faba bean diversity panels. Thus, the EUCLEG collection was the one showing lower LD blocks (higher recombination), an expected outcome in outbreeding species with high genetic diversity ( Pégard et al., 2023 ; Skovbjerg et al., 2023 ; Zanotto et al., 2023 ; Zhang et al., 2023 ). The rapid LD decay observed in this study (within roughly 150 kbp) revealed the variation present in a highly allogamous panmictic population and suggested that the MTAs identified (or the closely linked genes on either flanking side of the significant SNPs) were nearly or completely independent from each other and, hence, were sufficient for association mapping in faba bean.…”
Section: Discussionmentioning
confidence: 97%
“…Compared with family-based QTL mapping, GWAS significantly increases mapping resolution and enables minor effect genes to be detected ( Abdurakhmonov et al., 2008 ). In recent years, GWAS studies have been reported in a range of legume crops such as soybean ( Hwang et al., 2014 ), pigeon pea ( Varshney et al., 2017 ), common bean ( Raggi et al., 2019 ), chickpea ( Varshney et al., 2019 ), red clover ( Zanotto et al., 2023 ), alfalfa ( Pégard et al., 2023 ), and the model legume Medicago truncatula ( Bonhomme et al., 2014 ). In faba bean, only a few GWAS studies have been reported so far which have identified candidate genes associated with frost tolerance ( Sallam et al., 2016 ); resistance to Ascochyta fabae ( Faridi et al., 2021 ); tolerance to herbicides ( Abou-Khater et al., 2022 ); drought, heat, and freezing tolerance ( Ali et al., 2016 ; Maalouf et al., 2022 ; Gutiérrez et al., 2023 ); agronomic traits ( Skovbjerg et al., 2023 ); and seed size ( Jayakodi et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In breeding populations, PAs were found to vary between 0.21 – 0.66 depending on breeding cycle and location ( Li et al., 2015 ). Recently, Pégard et al. (2023) reported a mean PA of 0.65 for DMY from two locations, France and Serbia, and 0.41 for DOF in a diverse panel of alfalfa accessions, where the marker data also were obtained as allele frequencies derived from sequencing of pooled plant material representing each accession.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in ryegrass for prediction of flowering time, crown rust resistance, seed yield and fructan content ( Byrne et al., 2013 ; Fè et al., 2016 ; Cericola et al., 2018 ). Recently, GP was also successfully explored in alfalfa using pooled samples for genotyping ( Pégard et al., 2023 ). PA was above 0.75 for plant height and dormancy in some years, demonstrating the potential of GP for some traits.…”
Section: Introductionmentioning
confidence: 99%